Evaluation of Growth Performance and Improving Genetic Gain of Blue Tilapia (Oreochromis aureus) Fourth-generation (F-4) at Brackish Water Pond - Adam Robisalmi; Bambang Gunadi; Priadi Setyawan (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Reseacrh The study showed that the selected F-4 blue tilapia had a better growth pattern than the control (non-selection) F-4 blue tilapia The difference in performance between the two populations of blue tilapia is an illustration of the genetic improvement that is passed on from parents to offspring as a result of the selective breeding The realized heritability value of the weight character of F-4 blue tilapia in the high category There was an increase in growth in the F-4 blue tilapia population with a positive response to selection Abstract Breeding program in order to increase genetic improvement in blue tilapia have not been widely carried out at brackish water ponds. This study aimed to evaluate the increase in growth and genetic gain of F-4 blue tilapia from family selection in ponds with 25-30 gL-1 salinity. The parent used for the formation of F-4 is the selected parent F-3 and as a control using the non-selected parent F-3. Spawning was carried out in a full-sib mating design using the family selection method. The ratio of male and female broodstock is 1: 2. Spawning and nursery activities of F-4 blue tilapia are carried out in freshwater. The enlargement test was carried out in the net cage 5m x2.5m x1 m which was installed in the ponds with a salinity of 25-35 g l-1 for 120 days, at a stocking density of 10 fish m-2. At the end of maintenance, a selection process is carried out on the weight traits. Parameters observed included growth, survival, and genetic values. The results showed that the growth and survival in the F-4 blue tilapia population, male and female selected populations, had a higher value than in the non-selected population. The realized heritability value of the population growth character of the F-4 blue fish is in the high category. The difference in the average weight of the selected blue tilapia and the control was equivalent to an increase in genetic value added by 15.06% (male population) and 17.92% (female population).